Second Documentary Film for Enable Youth Program - الفيلم التوثيقي الثاني لبرنامج تمكين الشباب - International Institute of Tropical Agriculture (ENABLE Youth Sudan, 2020)
هذا الفيلم يوثق لفترة الانتاج التجريبي داخل حاضنات الاعمال لكل سلاسل القيمة في الولايات الخمس المستهدفة والتي من خلالها تم اعداد رواد الاعمال الزراعيين لدخول مجال الاعمال الزرعية. This film documents the pilot production in business incubators for all the value chains in the five targeted states through which agripreneurs are prepared to enter the agribusiness.